PHP‐based collaborative education and management system for water hydraulic laboratory - Wang, Haihang; Xu, He; Li, Qiang; Fu, Yu (Computer applications in engineering education, 2018)
Online learning platforms are becoming increasingly popular in engineering education. Through combining the educational form of online learning with laboratory information management systems (LIMS), we can integrate the education and management functions into one system. The purpose of this study is to develop a collaborative education and management system for the water hydraulic laboratory based on the Hypertext Preprocessor (PHP) scripting language. The system provides a convenient and multifunctional education and management platform for students and teachers throughout the whole experiment courses. Additionally, the B/S (Brower/Server) structure based on the Model‐View‐Controller (MVC) model was used in our system. The key steps of developing the WathyLab system were described, and the practical application subjects regarding water hydraulic materials were illustrated. The paper ends with an evaluation of this system according to the questionnaire survey. The students’ attitudes were surveyed and analyzed. Results showed that the proposed system can lead to better education effectiveness and learning efficiency.